1981
DOI: 10.1007/bf00163770
|View full text |Cite
|
Sign up to set email alerts
|

The expenditure effects of municipal annexation

Abstract: Analyzing the provision of local public services in the context of a market for local government services has yielded numerous important insights into local first behavior (Martin and Wagner, 1978;Martin, 1977;Wagner and Weber, 1975). Any change in local government structure -institutional or legal -can be examined for its effect on the competitive conditions in this market and the degree to which it promotes or retards centralization (monopoly) in the provision of government services. The major advantage of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
0
21
0
2
Order By: Relevance
“…NOTES 1. Mehay (1981) has analyzed the expenditure effects of annexation under the Local Agency Formation Commissions in California. This paper extends and improves that research in several ways: (1) we develop a formal behavioral model to analyze the effects of annexation;…”
Section: Discussionmentioning
confidence: 99%
“…NOTES 1. Mehay (1981) has analyzed the expenditure effects of annexation under the Local Agency Formation Commissions in California. This paper extends and improves that research in several ways: (1) we develop a formal behavioral model to analyze the effects of annexation;…”
Section: Discussionmentioning
confidence: 99%
“…Percent changes in total municipal revenues and expenditures per capita are common dependent variables in annexation research (Cho, 1969;Edwards & Xiao, 2009;Gonzalez & Mehay, 1987;Liner, 1992;Liner (2) MacGregor, 2002;Mehay, 1981). They offer a way to assess differences in the relative growth in revenues and spending between annexers and non-annexers.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Metropolitan government reformists view suburbanization and fragmentation of local governments as the fundamental problem of urban areas that results in the out‐migration of the rich to the suburbs and leaves the economically disadvantaged behind (Briffault, ; Rusk, , ; Stephens & Wikstrom, ). From this perspective, annexation improves municipal efficiency through economies of scale and lessens fiscal inequities by reducing tax base disparities (Edwards & Xiao, ; Liner, ; Mehay, ; Rusk, ; Stephens & Wikstrom, ). As a result of annexation, revenues go up, while spending decreases due to economies of scale.…”
Section: Why Annex?mentioning
confidence: 99%
“…In his earlier analysis of over four hundred cities, Liner (1992) found that annexation activity is inversely associated with the growth of per capita police and fire expenditures and with municipal employment. This contrasted with the conclusions reached by Gonzalez and Mehay (1987) and Mehay (1981). Gonzalez and Mehay examined over three hundred cities in twenty-four southern and western states and found that cities with higher rates of annexation have higher expenditures per capita and higher municipal taxes.…”
Section: Fiscal Impacts Of Annexationmentioning
confidence: 48%